Loss to specialist follow-up in congenital heart disease; out of sight, out of mind. Issue 7 (20th December 2012) - Wray, Jo; Frigiola, Alessandra; Bull, Catherine; ,
Abstract : Objective: To evaluate the scale and clinical importance of loss to follow-up of past patients with serious congenital heart disease, using a common malformation as an example. To better understand the antecedents of loss to specialist follow-up and patients' attitudes to returning. Design: Cohort study using NHS number functionality. Content and thematic analysis of telephone interviews of subset contacted after loss to follow-up. Patients, intervention and setting: Longitudinal follow-up of complete consecutive list of all 1085 UK patients with repair of tetralogy of Fallot from single institution 1964–2009. Main outcome measures: Survival, freedom from late pulmonary valve replacement, loss to specialist follow-up, shortfall in late surgical revisions related to loss to follow-up. Patients' narrative about loss to follow-up. Results: 216 (24%) of patients known to be currently alive appear not to be registered with specialist clinics; some are seen in general cardiology clinics. Their median age is 32 years and median duration of loss to follow-up is 22 years; most had been lost before Adult Congenital services had been consolidated in their present form. 48% of the late deaths to date have occurred in patients not under specialist follow-up. None of those lost to specialist follow-up has had secondary pulmonary valve replacement while 188 patients under specialist care have. Patients lost to specialist follow-up who were contacted by telephone had no knowledge of its availability. Conclusions: Loss to specialist follow-up, typically originating many years ago, impacts patient management.